Optimizing Treatment for Severe-Early Childhood Caries: The Role of Groper’s Appliance - Uprety, Anjani; Dali, Mamta; Koirala, Bandana; Birajee, Gajendra (Nepal Journal of Health Sciences, 2024)
Severe-Early Childhood Caries (S-ECC), often leading to serious health issues if left untreated, possesses a great restorative challenge to the pediatric dentist. This case report discusses a comprehensive management of S-ECC in a 5-year-old female patient with high dental caries risk. The patient presented with multiple carious lesions, root stumps, and fenestrated roots, necessitating a staged intervention. Treatment involved restorations with glass ionomer cement, pulpectomy followed by omega loop post build-up on anterior tooth and stainless-steel crowns on posterior teeth. Additionally, extractions were performed and Groper’s appliance was inserted for esthetic rehabilitation and space maintenance on maxillary anterior and posterior regions, respectively. Following completion of the planned treatment, overall risk assessment measured low. This case report emphasizes the importance of rehabilitative interventions in S-ECC, showcasing Groper's appliance as a viable and effective treatment option.